PENGEMBANGAN KOMIK DIGITAL INTERAKTIF (EDUVENTURE) BERPENDEKATAN MEANINGFUL LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD - Ni Kadek Juni Dian Aristi; Dr. Gusti Ayu Putu Sukma Trisna; I Kadek Edi Yudiana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Low critical thinking skills among elementary school students remain an important issue in science and social studies (IPAS) learning due to the use of conventional, less interactive learning media that fail to connect learning materials with students’ real-life experiences, resulting in less meaningful learning. This condition affects students’ engagement and their ability to analyze, evaluate, and draw conclusions. This study aimed to develop an interactive digital comic media (Eduventure) based on a meaningful learning approach and to examine its validity, practicality, and effectiveness in improving the critical thinking skills of fourth-grade elementary school students. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants were fourth-grade students of SD Negeri 3 Kalibukbuk. Data were collected through media and material expert validation questionnaires, teacher and student response questionnaires, and critical thinking skills tests (pretest and posttest). Data were analyzed using descriptive quantitative techniques, normality and homogeneity tests, Paired Sample T-Test, and N-gain score analysis. The results showed that the interactive digital comic media (Eduventure) based on meaningful learning achieved a very high level of validity, was highly practical according to teacher and student responses, and was effective in improving students’ critical thinking skills, as indicated by significant differences between pretest and posttest results and an increase in scores with an adequate effectiveness category. Therefore, this media is suitable for use as an alternative IPAS learning medium to enhance elementary school students’ critical thinking skills. ABSTRAK Rendahnya kemampuan berpikir kritis siswa sekolah dasar menjadi permasalahan penting dalam pembelajaran IPAS akibat penggunaan media yang masih konvensional, kurang interaktif, dan belum mengaitkan materi dengan pengalaman nyata siswa sehingga pembelajaran kurang bermakna. Kondisi ini berdampak pada rendahnya keterlibatan siswa serta kemampuan menganalisis, mengevaluasi, dan menarik kesimpulan. Penelitian ini bertujuan mengembangkan media komik digital interaktif (Eduventure) berpendekatan meaningful learning serta menguji validitas, kepraktisan, dan keefektifannya dalam meningkatkan kemampuan berpikir kritis siswa kelas IV SD. Penelitian menggunakan pendekatan Research and Development (R&D) dengan model ADDIE yang meliputi analysis, design, development, implementation, dan evaluation. Subjek penelitian adalah siswa kelas IV SD Negeri 3 Kalibukbuk. Data dikumpulkan melalui angket validasi ahli media dan materi, angket respons guru dan siswa, serta tes kemampuan berpikir kritis (pretest dan posttest). Analisis data dilakukan menggunakan teknik deskriptif kuantitatif, uji normalitas, homogenitas, Paired Sample T-Test, dan N-gain score. Hasil penelitian menunjukkan bahwa media komik digital interaktif (Eduventure) berpendekatan meaningful learning memiliki kualifikasi sangat valid, sangat praktis berdasarkan respons guru dan siswa, serta efektif meningkatkan kemampuan berpikir kritis siswa yang ditunjukkan oleh perbedaan signifikan antara hasil pretest dan posttest serta peningkatan nilai dengan kategori efektivitas memadai. Dengan demikian, media ini layak digunakan sebagai alternatif pembelajaran IPAS untuk meningkatkan kemampuan berpikir kritis siswa sekolah dasar.